MODEL STRUKTURAL SISTEM INFORMASI MANAJEMEN RUMAH SAKIT BERDASARKAN FRAMEWORK HOT-FIT MODEL - Sinaga, Rotua Novita; Mitra, Mitra; Yunita, Jasrida; Renaldi, Reno; Efendi, Ahmad Satria (Poltekkes Kemenkes Bandung, 2025)
Hospital Management Information Sistem (HMIS) aims to enhance operational efficiency and healthcare service quality through the integration of patient data, electronic medical records, and resource management. However, its implementation in many hospitals is still hindered by infrastructure limitations, human resource readiness, and sistem interoperability, preventing optimal functionality. Strengthening policies, enhancing human resource capacity, and technological support are essential for effective HMIS implementation. This study aims to develop a structural model of HMIS based on the HOT-fit framework. A quantitative research approach with a cross-sectional design was employed. The study population comprised professionals (doctors, nurses, administrative staff) whose involvement with HMIS met the inclusion criteria, totaling 56 participants. The questionnaire used was validated for reliability and validity. Data were analyzed using SEM-PLS4 for students. The results indicate that service and technology quality significantly impact HMIS effectiveness, providing a basis for hospital management to improve human resource training and technological investment. The HOT-fit framework integrates Human, Organization, and Technology elements to assess the alignment of information sistems with organizational needs. Indirect effects were found, showing that the relationship between human and organizational factors on benefits is mediated by technology. The structural model of HMIS, based on the HOT-fit framework, achieved an SRMR value of 0.073 (<0.08), indicating a good model fit. The study concludes that the structural model of HMIS based on the HOT-fit framework provides a validated approach to improving sistem implementation in hospitals. Future research could focus on evaluating this model across various hospital settings to ensure broader applicability